Upaya Peningkatan Literasi Melalui Media Majalah Dinding ( Mading ) Berbasis Kearifan Lokal Oleh Mahasiswa Kampus Mengajar di SD N Tambakromo 1 - Aviani, Ranita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
One of the fundamental problems in Indonesia is the low level of public literacy. In order to increase literacy in Indonesia, the government created the National Literacy Movement (GLN) program which consists of the School Literacy Movement (GLS), the Family Literacy Movement, and the Community Literacy Movement. To support these activities, the Ministry of Education and Culture has again launched a new policy called Freedom to Learn on an Independent Campus (MBKM), one of its programs, namely Campus Teaching which focuses on increasing literacy and numeracy in schools. One of the efforts made by campus teaching students to increase school literacy at SD N Tambakromo 1 is by making a magazine with the theme of local wisdom. The method used in this study is descriptive qualitative method, which is a data collection technique by means of observation and interviews. From the results of the research conducted, it shows that there is an increase in literacy in students at SDN Tambakromo 1 through bulletin boards with the theme of local wisdom. This is due to the students' interest in local culture or wisdom which is used as a bulletin with their own creativity. In addition to increasing students' literacy in making magazines, it also increases the creativity and skills of students at SDN Tambakromo 1. Keywords: Literacy, Media, Local Wisdom